Embraces are lateralized in spider monkeys (Ateles fusciceps rufiventris). Issue 6 (27th March 2017) - Boeving, Emily R.; Belnap, Starlie C.; Nelson, Eliza L.
Abstract : Side biases observed in behavior are thought to reflect underlying asymmetric brain function or hemispheric specialization. Previous work in multiple species identified left side biases (associated with the right hemisphere) for processing social behavior. In highly social species such as primates, many behaviors may be categorized as social, yet differences between such behaviors have not been examined as a test of asymmetric brain function. Using Colombian spider monkeys ( Ateles fusciceps rufiventris ), we observed lateral positioning during two types of behaviors widely categorized as social affiliative: embracing and grooming, and identified a left bias for embracing, but not grooming. Our findings partially support prior research in hemispheric specialization, but suggest that there may be differences between social behaviors that drive specialization. We discuss these results in light of current theory on hemispheric specialization and highlight differences between embracing and grooming. Abstract : A left side bias was found for embraces in spider monkeys, while there was a trend toward a right bias in grooming. Lateralization patterns may be related to the difference in arousal implicated in risk (i.e., embraces) and routine (i.e., grooming) behaviors.